Transformative learning as a metatheory: definition, criteria, and typology - Hoggan, Chad D (Adult education quarterly, 2016)
This article addresses a significant problem with transformative learning theory; namely, that it is increasingly being used to refer to almost any instance of learning. This article offers several points of clarity to resolve this problem. First, it portrays a subtle but important evolution in the way the theory has been used in the literature and, as a solution, positions transformative learning as an analytic metatheory. It then presents a typology of transformative learning outcomes as a conceptual tool scholars can use to describe learning phenomena. Finally, this article suggests a definition and criteria for transformative learning to provide parameters around the phenomena that the metatheory of transformative learning should address.